Digestibility of triticale by Nile tilapia - Tachibana, Leonardo; Gonçalves, Giovani Sampaio; Guimarães, Igo Gomes; Pezzato, Luiz Edivaldo [UNESP] (My University, 2010)
This work aimed to determine the dry matter (DM), crude protein (CP), gross energy (GE) and essential aminoacid (EAA) digestibility coefficient of triticale by Nile tilapia. Fish with 112.00 ± 22.00g average weight were used to digestibility test. Reference diet was formulated with purified ingredients and triticale replaced 30% of this diet. Chromic oxide was used as an external inert marker to determine the digestibility coefficients. The apparent digestibility coefficients (ADC) of triticale were (%): 70.98; 87.33 ± 1.64; 72.87 ± 0.35; DM, CP and GE, respectively; alanine 80.45; arginine 94.88; aspartic acid 84.59; glycine 83.82; isoleucine 84.08; leucine 89.43; lysine 83.70; cysteine 99.87; methionine 76.38; phenylalanine 91.04; tyrosine 78.61; threonine 76.83; tryptophan 87.10; proline 97.64; valine 88.05; histidine 93.52; serine 87.76. Results demonstrated good quality of triticale nutrients to Nile tilapia feeds.
Digestibilidade aparente do triticale para a tilápia-do-Nilo
Keywords: Fish culture; Fishes; Oreochromis niloticus; Triticum turgisecale